Hypotension as a symptom of autonomic neuropathy in patients with advanced malignancies - Kohutek, Filip; Katrlik, Jaroslav; Bystricky, Branislav (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2019)
AIMS: Hypotension can be a symptom of paraneoplastic autonomic neuropathy (PAN). Onconeural antibodies (OA) provide strong evidence for the paraneoplastic origin of neurological syndromes. Our goal was to assess the frequency of PAN among patients with advanced malignancies and hypotension using OA. METHODS: Patients with advanced malignancies and hypotension were screened and enrolled as per protocol. Plasma levels of six classical OAs were assessed in these patients. We prospectively evaluated other symptoms of PAN in these patients. RESULTS: 31 patients out of 740 screened met the criteria of this cross-sectional study. OAs were present in 4 patients (12.9%). Anti-amphiphysin was found in 1 patient (3.23%), anti- CV2 (anti-CRPM5, anti- collapsin- response mediator protein) was present in 1 patient (3.23%), 1 patient (3.23%) was positive for anti-Hu and anti-Ma2 was present in 1 patient (3.23%). No patient was positive for 2 or more OAs. Normalization of blood pressure in concordance with partial remission occurred in 5 patients. The most used criteria for PAN were fulfilled in 9 patients. CONCLUSION: The frequency of PAN may be underestimated in a busy oncology clinic. Assessing OAs may aid in the differential diagnosis of hypotension of unknown origin.
Keywords: hypotension; Autoantibodies; Humans; lidé středního věku; onconeural antibodies; Biomarkers, Tumor; Nervous System Diseases; Female; Aged; dospělí; senioři; lidé; nádorové biomarkery; Adult; Neoplasm Metastasis; neurological disorders; metastázy nádorů; ženské pohlaví; Male; autoprotilátky; Middle Aged; nemoci nervového systému; Neoplasms; Aged, 80 and over; hypotenze; autonomní nervový systém; nádory; Cross-Sectional Studies; senioři nad 80 let; Autonomic Nervous System; Hypotension; mužské pohlaví; malignancy; průřezové studie